Presoja primernosti načrtovanih vrtičkarskih območij v Ljubljani - Bole, David (Urbani izziv, 2009)
This article examines garden plots in Ljubljana to present the planning of this self-sufficient vegetable production activity, which developed mostly spontaneously in all urban environments in and around Ljubljana. Some residents of Ljubljana, the Slovenian capital, are involved in this activity not so much because of economic necessity but because it provides recreation and relaxation, meets their need for direct contact with nature, and offers them an opportunity to produce healthy food. Typically, older people are involved in this activity, among which the number of highly educated people isunexpectedly high. The majority are happy with the plot-gardening situation.The city government has begun systematically removing garden plots in unsuitable locations, and has drafted a proposal to organize gardening areas in a way that does not pollute the environment, and at the same time provide them with suitable infrastructure. We evaluated the appropriateness ofthe planned locations in the draft City Municipality of Ljubljana Zoning Implementation Plan on the basis of the fulfillment of key exclusion and attraction criteria that were established based on survey answers included in support of the decision-making with the help of GIS tools. Decision-making by consensus, inclusion of public stakeholders, and establishing dialog between the city government and garden-plot users will need to be ensured in carrying out this plan.
Keywords: Ljubljana; prostorsko planiranje; spatial planning; urbanistično planiranje; vrtičkarstvo; vrtovi